The mediating effect of allostatic load on the association between life course socioeconomic disadvantage and chronic pain: a prospective finding from the National Survey of Midlife Development in the United States - Liang, Yunlong (Frontiers in Pain Research, 2023)
Background: Socioeconomic disadvantages (SED) are associated with chronic pain (CP) and allostatic load (AL). Few prospective population-based studies have examined the relationship between lifetime SED, CP interference and CP widespreadness, and there is no prospective population-based study on whether AL mediates the association between SED and CP.Objective: In this study, we investigated whether the prospective effect of SED on CP at MIDUS 3 is consistent with the accumulation of risk model and social mobility model, using national survey of Midlife Development in the U.S. (MIDUS, n=593). In preparation for the mediation analysis, we tested 1) whether SED would be prospectively associated with AL at MIDUS 2 biomarker project, 2) whether AL would be prospectively associated with CP, and whether childhood as a critical period moderated the association between AL and CP. Finally, the mediating effect of AL on the association between SED and CP was examined.Method: SED was measured by cumulative scores and disadvantage trajectories derived from latent class trajectory modeling (LCTM). After multiple imputations, analyses were conducted using multinomial logistic regression for CP and negative binomial regression for AL respectively. Finally, mediation analyses and moderated mediation analyses were conducted.Results: LCTM identified three SED trajectories including constant low SED, high-to-low SED, medium-to-high SED. The results showed that proximal cumulative SED was associated with highinterference CP. Furthermore, compared to the constant low SED group , the medium-to-high SED group was significantly associated with high interference pain and no fewer than three pain sites. Cumulative SED and deteriorating SED trajectories were associated with higher AL, consistent with previous studies. Furthermore, childhood SED moderated the effect of AL on CP widespreadness and unexpectedly demonstrated a protective effect, while other associations between AL and CP were not significant. Subsequent mediation analysis did not find statistically significant evidence.